Determinan Employee Engagement: Pengembangan Karir, Kompensasi, dan Lingkungan Kerja - Nafiudin Nafiudin; Ayu Chairani; Andari Andari; M. Nurhaula Huddin (Penerbit Goodwood, 2025)
Purpose: This study examines the impact of career development, compensation, and work environment on honorary employees’ engagement at the Civil Service Police Unit (Satpol PP) of Banten Province. Methodology/approach: Using a quantitative method, 58 respondents were selected from a population of 140 honorary employees through Slovin's formula with a 10% margin of error. Data were collected via an online survey and analyzed using PLS-SEM with SmartPLS 4. The analysis included both reflective (validity and reliability tests) and formative model assessments (multicollinearity and weight significance tests), followed by hypothesis testing using inner model evaluation. Results/findings: The bootstrapping results show that career development, compensation, and work environment each have a significant and positive effect on employee engagement. Conclusion: Structured career development fosters emotional commitment, fair compensation builds loyalty, and a supportive work environment enhances employee engagement. Institutions are encouraged to improve these aspects, along with promoting inclusive culture and effective communication. Limitations: Future studies should consider additional or mediating variables and involve larger samples for broader insights. Contribution: This study contributes to public sector HRM by identifying key drivers of engagement among honorary employees.